The effect of learning preferences on learners' motivations: towards an ARCS motivational design in open learner models - Sek, Yong Wee; McKay, Elspeth; Deng, Hepu (Institute Of Electrical And Electronics Engineers Inc. (IEEE), 2016)
Various motivational designs have been introduced to improve learners' motivations in engaging with technology-mediated learning. This study presents an investigation of the impact of learning preferences on their motivations towards the attention, relevance, confidence, and satisfaction (ARCS) motivational design in an open learner model (OLM) environment. Data was collected from undergraduate students in a university in Malaysia by using an online survey. A chi-square test was performed to explore the relationship between learning preferences and motivations in a higher education setting. The result reveals that an ARCS motivational design can impact learners' motivations towards the adoption of open learner models. The implications of this study will assist educational institutions to develop more effective and efficient policies for improving the adoption of open learner models in technology-mediated teaching and learning.